Glass-ceramics, tempered glass and preparation method and application thereof
A glass-ceramic with controlled spinel crystal phase and oxide ratios addresses high melting temperatures and material costs, achieving high transmittance and mechanical strength for electronic display devices.
Patent Information
- Application Number
- CN202311109673.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-08-31
AI Technical Summary
Existing glass-ceramics face challenges with high melting temperatures, high raw material costs, and suboptimal mechanical and optical properties, limiting their application in electronic display devices.
A glass-ceramic composition with a spinel crystal phase and specific oxide ratios (SiO2, Al2O3, MgO, ZnO, ZrO2, TiO2, and Li2O) is developed, allowing for lower melting temperatures and improved mechanical and optical properties through controlled crystallization and chemical strengthening.
The glass-ceramic achieves high transmittance, low haze, and enhanced mechanical strength, with ion exchange depth and compressive stress, suitable for electronic display devices.
Smart Images

Figure CN117125897B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular to a glass-ceramic, tempered glass, and a preparation method and application thereof. Background Art
[0002] With the continuous development of digital informationization in various industries, people have put forward higher and higher requirements for the lightweight and service life of electronic display devices. As one of the important materials to protect the screen of display devices from direct contact with the external environment, electronic cover glass has high requirements for its optical and mechanical properties. The performance of traditional ordinary high-aluminum glass is close to the limit range of materials, and the performance can be improved to a low extent. However, due to the existence of crystal phase, microcrystalline glass has excellent mechanical properties and can meet the market demand for cover glass in various environments and different situations.
[0003] The existing glass-ceramics on the market are mainly lithium aluminum silicate (LAS) systems, but the price of the raw material lithium carbonate is too high, which limits the large-scale application of this system of glass-ceramics. In order to meet the market demand for glass-ceramics, there are also many studies dedicated to improving the glass-ceramics process. For example, CN202111056618.6 provides a transparent magnesium aluminum silicon glass-ceramics, but the melting temperature of the glass is high>1650℃, the hardness is low<714HV, and Sb is added. 2 O 3 and other non-environmentally friendly clarifiers; CN202010009864.5 and CN202210737448.6 both provide a spinel transparent glass-ceramics, but they also have the problem of high melting temperature, and perform poorly in terms of transmittance, ion exchange depth, and mechanical properties after strengthening. Summary of the invention
[0004] Based on this, the present application provides a microcrystalline glass and a preparation method thereof that can both reduce the melting temperature and improve the transmittance of the glass.
[0005] Furthermore, an embodiment of the present application also provides a tempered glass capable of improving ion exchange depth and mechanical properties and a preparation method thereof.
[0006] Furthermore, an embodiment of the present application also provides applications of the microcrystalline glass and the tempered glass.
[0007] An embodiment of the present application provides a glass-ceramic, comprising a spinel crystal phase with a crystallinity of >20%;
[0008] In terms of mass percentage, the composition of glass-ceramics includes:
[0009] 35%≤SiO 2 ≤55%、
[0010] 15%≤Al 2 O 3 ≤35%,
[0011] 0%≤Li 2 O<1%、
[0012] 0%≤MgO≤10%,
[0013] 0%≤Na 2 O≤15%,
[0014] 5%≤ZnO≤15%,
[0015] 0%≤ZrO 2 ≤6%, and
[0016] 0%≤TiO 2 ≤6%;
[0017] The mass percentage of the composition of the microcrystalline glass meets the following conditions:
[0018] SiO 2 +Al 2 O 3 ≥67%, 3%≤ZrO 2 +TiO 2 ≤8%,
[0019] MgO+ZnO≤16%,Li 2 O / (MgO+ZnO)≤0.11.
[0020] In one embodiment, the microcrystalline glass also contains zirconium oxide crystal phase and / or spodumene crystal phase.
[0021] In one embodiment, the microcrystalline glass contains the zirconium oxide crystal phase, and the crystallinity of the zirconium oxide crystal phase is less than 15%.
[0022] In one embodiment, the glass-ceramics contains the spodumene crystal phase, and the crystallinity of the spodumene crystal phase is less than 0.5%.
[0023] In one embodiment, the average diameter of the grains is 10 nm to 70 nm.
[0024] In one embodiment, the composition of the glass-ceramics includes, by mass percentage:
[0025] 40%≤SiO 2 ≤55%、
[0026] 20%≤Al 2 O 3 ≤35%,
[0027] 0%≤Li2 O<1%、
[0028] 1%≤MgO≤8%,
[0029] 2%≤Na 2 O≤13%,
[0030] 5%≤ZnO≤12%,
[0031] 2%≤ZrO 2 ≤6%, and
[0032] 0%≤TiO 2 ≤6%.
[0033] An embodiment of the present application provides a method for preparing microcrystalline glass, comprising the following steps:
[0034] Weigh glass raw materials according to the composition of the glass-ceramics described in any of the above embodiments;
[0035] Melting the raw materials to prepare a glass melt;
[0036] Casting the glass melt to prepare a matrix glass;
[0037] The base glass is subjected to microcrystallization treatment to prepare the microcrystalline glass.
[0038] An embodiment of the present application also provides a method for preparing tempered glass, comprising the following steps:
[0039] The glass-ceramics described in any of the above embodiments is subjected to chemical strengthening treatment.
[0040] An embodiment of the present application further provides a tempered glass, which is prepared by the preparation method described in the above embodiment.
[0041] An embodiment of the present application further provides a use of the microcrystalline glass as described in any of the above embodiments, or the tempered glass as described in the above embodiment in the preparation of glass products.
[0042] The above-mentioned microcrystalline glass adopts a glass composition with a specific mass percentage and spinel as the main crystal phase. It can be produced through a lower melting temperature. The average transmittance of the microcrystalline glass is high and the haze is low. After chemical strengthening, the strengthened glass formed has a high ion strengthening depth and good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a SEM scanning electron microscope morphology of the crystal phase of the glass-ceramic sample of Example 1;
[0044] Figure 2 This is the XRD diagram of the glass-ceramic sample of Example 4. DETAILED DESCRIPTION
[0045] For ease of understanding of the present application, the present application will be described more fully below in conjunction with embodiments and accompanying drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described in the present application. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0046] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more related listed items.
[0047] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0048] Some embodiments of the present application provide a glass-ceramic comprising a spinel crystal phase with a crystallinity greater than 20%.
[0049] Spinels such as magnesium aluminum, zinc aluminum, magnesium zinc spinel, etc. have the general formula AB 2 O 4 The prototype spinel structure is magnesium aluminate (MgAl 2 O 4 ). In the basic spinel structure, O atoms fill the face-centered cubic (FCC) array sites, which have extremely high mechanical properties. Controlling the crystallinity of the spinel main crystal phase to exceed 20% can make microcrystalline glass and strengthened glass have higher mechanical strength.
[0050] In terms of mass percentage, the composition of glass-ceramics includes:
[0051] 35%≤SiO 2 ≤55%、
[0052] 15%≤Al 2 O 3 ≤35%,
[0053] 0%≤Li 2 O<1%、
[0054] 0%≤MgO≤10%,
[0055] 0%≤Na 2 O≤15%,
[0056] 5%≤ZnO≤15%,
[0057] 0%≤ZrO 2 ≤6%, and
[0058] 0%≤TiO 2 ≤6%.
[0059] The mass percentage of the composition of glass-ceramics meets the following conditions:
[0060] SiO 2 +Al 2 O 3 ≥67%, 3%≤ZrO 2 +TiO 2 ≤8%,
[0061] MgO+ZnO≤16%,Li 2 O / (MgO+ZnO)≤0.11.
[0062] In some embodiments of the present application, the composition of the microcrystalline glass contains 35% to 55% by mass of SiO 2 .SiO 2 It is the main oxide used to form glass and can be used to stabilize the network structure of microcrystalline glass by limiting SiO 2 The content of SiO2 in the above range can control the melting temperature (200 poise temperature) of the glass raw materials and avoid the melting temperature being too high or too low. Preferably, the composition of the microcrystalline glass contains 40% to 55% by mass of SiO2. 2 .
[0063] In some embodiments of the present application, the composition of the microcrystalline glass contains 15% to 35% by mass of Al 2 O 3 .Al 2 O 3 It can also stabilize the glass network and also has the effect of improving the mechanical properties and chemical durability of the glass. 2 O 3 The mass percentage of Al 2 O 3 The concentration is high enough to form a spinel phase, and the residual glass phase also contains Al 2 O 3 It can be used to enhance the capacity of Li-Na and Na-K ion exchange; at the same time, due to Al 2 O 3 The melting temperature is high and it can be used as a network intermediate. 2 O 3 The content of Al can control the viscosity of the glass melt. 2 O 3Too high a content of Al will increase the melt viscosity and reduce the glass-forming ability of the glass melt. 2 O 3 The mass percentage of Al is within the appropriate range, which can ensure that the glass melt has an appropriate melt temperature and a good glass-forming ability. Preferably, the composition of the microcrystalline glass contains 20% to 35% Al by mass. 2 O 3 . Further, the mass percentage of SiO 2 +Al 2 O 3 ≥67%, which can ensure that the microcrystalline glass structure is sufficiently stable. In some embodiments of the present application, the composition of the microcrystalline glass contains MgO and ZnO. MgO and ZnO are alkaline earth metal oxides, which can be used to reduce the high-temperature viscosity of the matrix glass and modify the glass structure, thereby improving the strength and chemical stability of the matrix glass. At the same time, MgO is also one of the important components of the main crystalline phase spinel. Furthermore, the mass percentage of MgO is 0% to 10%. If the MgO content is too high, the high-temperature viscosity of the melt will increase, making the melting more difficult, and it will also make the formation process of the spinel crystal phase difficult to control and the grain size will be too large, which is not conducive to improving the transmittance of the glass. Preferably, the mass percentage of MgO is 1% to 8%. Furthermore, the mass percentage of ZnO is 5% to 12%. Due to the 2+ It has a high field strength accumulation effect in the glass melt. Adding ZnO will increase the crystallization tendency of the matrix glass and reduce the crystallization activation energy of the spinel crystal phase. However, the price of ZnO raw materials is relatively expensive. Like MgO, if the addition amount is too high, the crystallization tendency of the glass will increase. It is difficult to control the growth process of the crystal phase during the crystallization heat treatment, which can easily lead to excessive crystal size. In addition, a large amount of ZnO remains in the glass phase, which will reduce the performance of the glass and the Li-Na and Na-K ion exchange capacity. Therefore, MgO+ZnO is controlled to be ≤16.
[0064] The crystallization tendency of magnesium-aluminum-silicon system glass is low and the crystallization barrier is high. In some embodiments of the present application, TiO 2 and ZrO 2 Added as a nucleating agent, it can improve the crystallization ability of the glass melt and increase the liquidus temperature during the preparation of the glass. Furthermore, the composition of the microcrystalline glass contains 0% to 6% by mass of ZrO 2 and 0% to 6% TiO 2 By adding an appropriate amount of TiO 2 and / or ZrO 2 It can reduce the activation energy of crystallization, promote the precipitation of uniform crystal nuclei in the matrix glass, and generate the target crystal phase. 2It has a strong coloring ability, which will make the glass have a darker color, so it is not advisable to add too much; at the same time, a higher content of TiO 2 It will make the crystal growth in the matrix glass difficult to control, abnormally grow, generate more impurities, make the performance of microcrystalline glass or strengthened glass difficult to control, and easily cause cracking and significant performance degradation. 2 The solubility in glass melt is low and the melting temperature is extremely high. It is not advisable to add too much ZrO. 2 The crystal growth in the matrix glass will be difficult to control, abnormally grow, and more impurities will be generated. Preferably, the composition of the microcrystalline glass contains 2% to 6% by mass of ZrO 2 and 0% to 6% TiO 2 In order to ensure that a large number of evenly distributed nano-sized spinel, zirconium oxide, spodumene and other crystal phases are simultaneously precipitated in the matrix glass, so that the microcrystalline glass has high transmittance, further, the ZrO 2 and TiO 2 The mass percentage relationship satisfies 3% ≤ ZrO 2 +TiO 2 ≤8%.
[0065] Meanwhile, in some embodiments of the present application, by defining Li 2 The mass percentage relationship between O and MgO and ZnO satisfies Li 2 O / (MgO+ZnO)≤0.11. Under the condition that the above relationship is met, the content of spodumene crystal phase can be effectively controlled, so that the microcrystalline glass has excellent optical properties, and the alkali metal ion exchange capacity in the glass can be effectively balanced. The strengthened glass obtained after chemical strengthening has good stress properties.
[0066] Li 2 O and Na 2 The introduction of O is beneficial to lowering the melting temperature of the glass and is beneficial to the subsequent ion exchange. Among them, lithium ions have a strong accumulation effect due to their small ion radius, which helps to precipitate the target crystal phase to a certain extent. However, if the content is too high, a large amount of spodumene crystal phase will be precipitated, which will inhibit the precipitation of spinel crystal phase, reduce the transmittance of the sample and deteriorate the performance. Preferably, the composition of Li in the microcrystalline glass is 2 The mass percentage of O is 0% to 1%. 2 Too much O will inhibit the precipitation of the target spinel crystal phase, which is not conducive to crystal phase control. It is easy to precipitate impurities such as albite and sodium nepheline, causing the sample to lose transparency and reduce performance. Preferably, Na 2 The mass percentage of O is 0% to 15%, and more preferably, Na 2 The mass percentage of O is 2% to 13%.
[0067] In one embodiment, the microcrystalline glass further contains zirconium oxide crystal phase and / or spodumene crystal phase. Zirconium oxide crystal has extremely high mechanical properties (Mohs hardness>7.5) and is an ideal strengthening and toughening crystal phase in microcrystalline glass. 2 O 6 It belongs to the monoclinic system. The crystals are often columnar, granular or plate-like. The symmetry is 2 / m. The crystal structure is similar to diopside. It is one of the main lithium-containing minerals, also known as type 2 spodumene. The microcrystalline glass contains spodumene crystal phase and can be chemically strengthened in a salt bath. + and / or K + Will replace Li in the spodumene structure + , so that the glass surface can be compressed and strengthened, and the overall strength can be greatly improved.
[0068] Furthermore, the glass-ceramics contains a zirconium oxide crystal phase, and the crystallinity of the zirconium oxide crystal phase is less than 15%. 2 It is added as a nucleating agent in the glass composition. Too much crystalline phase content will easily lead to difficulty in controlling the grain size of the glass and inability to obtain transparent microcrystalline glass. Therefore, the crystallinity of zirconium oxide is controlled to be less than 15%.
[0069] Furthermore, the microcrystalline glass contains a spodumene crystal phase, and the crystallinity of the spodumene crystal phase is less than 0.5%. Controlling the crystallinity of spodumene to less than 0.5wt% can avoid the optical properties of the glass being affected by excessive spodumene crystal phase content, such as increasing haze and reducing transmittance.
[0070] In some embodiments of the present application, the average diameter of the crystal grains is 10 nm to 70 nm. Controlling the average diameter of the crystal grains within a specific range can avoid the optical properties of the glass being deteriorated due to the excessively large crystal grain size, such as increased haze and reduced transmittance.
[0071] In some embodiments of the present application, the composition of the glass-ceramics includes, by mass percentage:
[0072] 40%≤SiO 2 ≤55%、
[0073] 20%≤Al 2 O 3 ≤35%,
[0074] 0%≤Li 2 O<1%、
[0075] 1%≤MgO≤8%,
[0076] 2%≤Na 2 O≤13%,
[0077] 5%≤ZnO≤12%,
[0078] 2%≤ZrO 2 ≤6%, and
[0079] 0%≤TiO 2 ≤6%.
[0080] Some embodiments of the present application provide a method for preparing glass-ceramics, comprising the following steps S110 to S140.
[0081] S110: Weigh glass raw materials according to the composition of the glass-ceramics in any of the above embodiments.
[0082] The glass composition obtained by using glass raw materials according to mass percentage includes 35%≤SiO 2 ≤55%、15%≤Al 2 O 3 ≤35%、0%≤Li 2 O<1%, 0%≤MgO≤10%, 0%≤Na 2 O≤15%, 5%≤ZnO≤15%, 0%≤ZrO 2 ≤6%、0%≤TiO 2 ≤6%;
[0083] The mass percentage of the composition of the glass-ceramics meets the following conditions: SiO 2 +Al 2 O 3 ≥67%, 3%≤ZrO 2 +TiO 2 ≤8%, MgO+ZnO≤16%, Li 2 O / (MgO+ZnO)≤0.11.
[0084] S120: Melting raw materials to prepare a glass melt.
[0085] Furthermore, the melting temperature is 1300°C to 1550°C.
[0086] Furthermore, the melting time is 6 hours to 10 hours.
[0087] Furthermore, stirring may be performed during the melting process.
[0088] S130: Casting the glass melt to prepare a matrix glass.
[0089] Furthermore, the step of cooling the glass melt before casting may be included, preferably, cooling the temperature to 1200° C. to 1450° C. and keeping the temperature for 2 hours for homogenization.
[0090] Furthermore, the step of preheating the mold may be included before casting. Preferably, the mold is preheated to 400°C to 500°C.
[0091] Furthermore, after casting, the formed glass may be annealed. Preferably, the annealing conditions include: keeping the temperature at 400°C to 500°C for 1.5h to 2.5h, and then controlling the cooling rate to cool to 130°C to 150°C within 5h to 7h.
[0092] Furthermore, a natural cooling step may be included after annealing.
[0093] S140: performing microcrystallization treatment on the base glass to prepare microcrystalline glass.
[0094] Furthermore, the microcrystallization treatment step includes: firstly heat-treating the base glass for nucleation, and then heating it for crystallization.
[0095] Furthermore, the nucleation temperature is 600°C to 800°C.
[0096] Furthermore, the nucleation time is 0.5h to 10h.
[0097] Furthermore, the crystallization temperature is 700°C to 900°C.
[0098] Furthermore, the crystallization time is 0.1h to 4h.
[0099] It can be understood that the microcrystalline glass provided in the present application can be prepared by conventional glass processes, such as but not limited to float forming process, overflow down-draw method, pull-up method, flat-draw method, rolling method, etc.
[0100] Some embodiments of the present application also provide a method for preparing tempered glass, comprising the following steps:
[0101] The glass-ceramics in any of the above embodiments is subjected to chemical strengthening treatment.
[0102] Furthermore, the chemical strengthening treatment includes two chemical strengthening steps.
[0103] Furthermore, the step of the first chemical strengthening treatment includes: immersing the microcrystalline glass in a first molten liquid formed by at least one of sodium nitrate and potassium nitrate.
[0104] Preferably, in the first molten liquid, the mass ratio of sodium nitrate to potassium nitrate is (40-100):(0-60).
[0105] Preferably, the soaking conditions of the first chemical strengthening treatment include: soaking temperature of 440° C. to 500° C., and soaking time of 4 h to 16 h.
[0106] Furthermore, the step of the second chemical strengthening treatment includes: immersing the glass after the first chemical strengthening in a second molten liquid formed by at least one of sodium nitrate and potassium nitrate.
[0107] Preferably, in the second molten liquid, the mass ratio of sodium nitrate to potassium nitrate is (96-100):(4-0).
[0108] Preferably, the soaking conditions of the second chemical strengthening treatment include: soaking temperature of 380° C. to 440° C., and soaking time of 1 h to 4 h.
[0109] Some embodiments of the present application also provide a tempered glass, which is prepared by the preparation method in the above embodiment.
[0110] Some embodiments of the present application also provide a use of a microcrystalline glass as in any of the above embodiments, or a tempered glass as in one of the above embodiments, in the preparation of glass products.
[0111] It can be understood that the glass product can be, for example but not limited to, electronic glass, protective glass, photovoltaic glass, fireproof glass, architectural glass or other special glass, etc.
[0112] In some embodiments of the present application, the provided microcrystalline glass has an average transmittance of ≥85% and a haze of ≤1.8. After chemical strengthening, the tempered glass obtained in the present application can achieve excellent performances such as a compressive stress CS30 of more than 50 MPa at a depth of 30 μm, an overall compressive stress depth Dol_0 of more than 100 μm, a surface Mohs hardness of more than 7.5, a ring compression strength of more than 823 MPa, and a sandpaper drop height of more than 1.6 m.
[0113] The following specific examples further illustrate the glass-ceramics, tempered glass, and preparation methods and applications of the present application. The following examples are relatively specific, and it can be understood that they are not limited to these in other embodiments. In the following specific embodiments, the instruments, reagents, and materials involved, unless otherwise specified, are all conventional instruments, reagents, and materials already available in the prior art, and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods and detection methods already available in the prior art.
[0114] 1. Preparation of substrate glass:
[0115] The mass percentages of the various components of the microcrystalline glass in Examples 1 to 20 and Comparative Examples 1 to 4 are shown in Tables 1 to 3. According to the glass composition of each example, the corresponding glass raw materials are weighed, and after being fully mixed, they are melted in a platinum crucible at 1450°C for 8 hours to form a glass melt, and stirred with a platinum stirring paddle; after the stirring paddle is pulled out, the glass melt is cooled to 1320°C, and kept warm for 2 hours for homogenization; then the glass melt is cast into an iron mold to form a glass block of about 80mm×160mm in size, and the mold is preheated to 450°C before casting. After the glass block is hardened, it is immediately transferred to an annealing furnace for annealing, kept warm for 2 hours, and controlled to cool to 140°C within 6 hours, and naturally cooled to obtain the matrix glass, which is taken out and set aside.
[0116] The base glass samples of Examples 1 to 20 and Comparative Examples 1 to 4 were cut into glass sheets of 70 mm × 140 mm × 0.6 mm by a STX-1203 wire cutting machine produced by Shenyang Kejing, thinned and polished by a HD-640-5L double-sided grinding and polishing machine produced by Shenzhen Hyde, and then edged by CNC. The transmittance in the wavelength range of 380 nm to 780 nm was tested using a Lambda 950 UV-visible spectrophotometer produced by PerkinElmer, USA. The results are shown in Tables 1 to 3.
[0117] 2. Preparation of glass-ceramics
[0118] The base glass prepared in step 1 of the above-mentioned Examples 1 to 20 and Comparative Examples 1 to 4 is subjected to microcrystallization treatment according to the microcrystallization process parameters shown in Tables 1 to 3 to prepare microcrystalline glass.
[0119] The glass-ceramic samples obtained after crystallization in Examples 1 to 20 and Comparative Examples 1 to 4 were cut, and the cross-sections were ground and polished for later use. The glass-ceramic samples were cut into 20 mm × 20 mm pieces, and their crystalline phase types were tested by Bruker D8 advance X-ray diffractometer, and the proportions of different types of crystalline phases and amorphous phases were calculated by TOPAS software simulation, and recorded in Tables 1 to 3.
[0120] 3. Preparation of tempered glass
[0121] The glass-ceramics prepared in step 2 of Examples 1 to 20 and Comparative Examples 1 to 4 are subjected to a secondary strengthening process to prepare strengthened glass.
[0122] First chemical strengthening: The microcrystalline glass is immersed in a first molten liquid formed by at least one of sodium nitrate and potassium nitrate. The mass percentages of sodium nitrate and potassium nitrate in the first molten liquid and the immersion conditions are shown in Tables 1 to 3 below.
[0123] Second chemical strengthening: The glass after the first chemical strengthening is immersed in a second molten liquid formed by at least one of sodium nitrate and potassium nitrate. The mass percentages of sodium nitrate and potassium nitrate in the second molten liquid and the immersion conditions are shown in Tables 1 to 3 below.
[0124] The compressive stress CS30 and stress depth Dol_0 (μm) of the Li-Na exchange 30 μm depth in the tempered glasses prepared in Examples 1 to 20 and Comparative Examples 1 to 4 were tested by using a surface stress meter SLP2000 of Orihara Industries Co., Ltd., Japan. The surface Mohs hardness was tested by using a Mohs hardness pen. The transmittance in the wavelength range of 380 nm to 780 nm was tested by using a Lambda950 UV-visible spectrophotometer of PerkinElmer, USA. The haze of the samples was tested by using a SUGA Optical HZ-V3 haze meter. The ring compression strength (upper ring) was tested by using a PT-307A universal testing machine of Puset. Lower Ring ), the drop height of 180-grit sandpaper was tested using Shenzhen Gaopin's GP-2112-T directional drop tester, and the data are recorded in Tables 1 to 3 below.
[0125] Table 1 Glass composition, process parameters, and performance data of Examples 1 to 10
[0126]
[0127]
[0128] Table 2 Glass composition, process parameters, and performance data of Examples 11 to 20
[0129]
[0130]
[0131]
[0132]
[0133] Table 3 Glass composition, process parameters, and performance data of Comparative Examples 1 to 4
[0134]
[0135]
[0136] It can be seen from Tables 1 to 3 that the microcrystalline glasses of Examples 1 to 20 have spinel as the main crystal phase, have a high average transmittance and a low haze, and after chemical strengthening, the formed strengthened glass has a high ion strengthening depth and good mechanical properties.
[0137] In Comparative Example 1, Li 2 The mass percentage of O is 2%, greater than 0.95%, and
[0138] Li 2 O / (MgO+ZnO)=0.15, which is greater than 0.11; after crystallization, more spodumene crystal phases are precipitated and the grain size becomes larger, resulting in a decrease in glass transmittance and an increase in haze. After ion strengthening, the final manifestation is a decrease in ring pressure and drop resistance.
[0139] In Comparative Example 2, the mass percentage of MgO is 13%, which is greater than 10%, MgO+ZnO=18%, which is greater than 16%, and SiO 2 +Al 2 O 3 =65%, less than 67%; the magnesium oxide content increased, the silicon oxide and aluminum oxide contents decreased, which reduced the difficulty of impurity formation, precipitated more periclase impurities, inhibited the formation of spinel target crystal phase, and increased grain size, resulting in reduced sample transmittance and increased haze. After ion strengthening, the final manifestation was a decrease in strengthening stress, ring pressure and drop resistance.
[0140] In Comparative Example 3, the mass percentage of ZnO is 2%, which is less than 5%, and the mass percentage of TiO 2 The mass percentage is 8%, which is greater than 6%, ZrO 2 +TiO 2 =10%, greater than 8%; the zinc oxide content decreases, which weakens the tendency of spinel crystallization, and is prone to generate periclase impurities, and the grain size becomes larger, making it difficult to control its transmittance. In addition, the content of titanium oxide nucleating agent increases, the tendency of crystallization becomes larger, and periclase impurities are prone to appear, and the grain size is difficult to control. In addition, too high a titanium oxide content will color the glass and affect the transmittance of the glass; after ion strengthening, the final manifestation is the reduction of strengthening stress, ring pressure and drop resistance.
[0141] In Comparative Example 4, ZrO 2 +TiO 2 =2%, less than 3%, the nucleating agent content is too low, resulting in a low crystallization tendency of the glass sample and the inability to precipitate the crystal phase. After ion strengthening, the final manifestation is that the strengthening stress, ring pressure and drop resistance are all low.
[0142] Figure 1 The SEM scanning electron microscope morphology of the crystal phase of the glass-ceramic sample of Example 1 is shown. Figure 1 It can be seen that glass has a microcrystalline structure.
[0143] Figure 2 The XRD pattern of the glass-ceramic sample of Example 4 is shown. Figure 2 It can be seen that Example 4 contains both spinel and zirconia crystal phases, and spinel is the main crystal phase.
[0144] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0145] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of this application. Therefore, the protection scope of the patent of this application shall be subject to the attached claims.
Claims
1. A glass-ceramic, characterized in that: Contains spinel phase with crystallinity > 20%; In terms of mass percentage, the composition of glass-ceramics includes: 35%≤SiO2≤55%, 15%≤Al2O3≤35%, 0%<Li2O<1% 0%≤MgO≤10%, 0%≤Na2O≤15%, 5%≤ZnO≤15%, 0%≤ZrO2≤6%, and 0%≤TiO2≤6%; The mass percentage of the composition of the microcrystalline glass meets the following conditions: SiO2+Al2O3≥67%, 3%≤ZrO2+TiO2≤8%, MgO+ZnO≤16%, Li2O / (MgO+ZnO)≤0.11; The microcrystalline glass contains a spodumene crystal phase, and the crystallinity of the spodumene crystal phase is 0.1%≤0.5%; The average transmittance of the microcrystalline glass is ≥85%, and the haze is ≤1.
8.
2. The glass-ceramic according to claim 1, characterized in that: The microcrystalline glass contains a zirconium oxide crystal phase, and the crystallinity of the zirconium oxide crystal phase is 2%≤<15%.
3. The glass-ceramic according to claim 1, characterized in that: The average grain diameter is 10nm~70nm.
4. The glass-ceramics according to any one of claims 1 to 3, characterized in that: The composition of the glass-ceramics includes, by mass percentage: 40%≤SiO2≤55%, 20%≤Al2O3≤35%, 0%<Li2O<1%, 1%≤MgO≤8%, 2%≤Na2O≤13%, 5%≤ZnO≤12%, 2%≤ZrO2≤6%, and 0%≤TiO2≤6%.
5. A method for preparing glass-ceramics, characterized in that: The steps include: Weigh glass raw materials according to the composition of the glass-ceramics according to any one of claims 1 to 4; Melting the raw materials to prepare a glass melt; Casting the glass melt to prepare a matrix glass; The base glass is subjected to microcrystallization treatment to prepare the microcrystalline glass.
6. The method for preparing glass-ceramics according to claim 5, characterized in that: The melting temperature is 1300°C to 1550°C, and the melting time is 6h to 10h.
7. The method for preparing glass-ceramics according to claim 5, characterized in that: The steps of microcrystallization treatment include: firstly heat-treating the base glass for nucleation, and then heating it for crystallization.
8. The method for preparing glass-ceramics according to claim 7, characterized in that: The nucleation temperature is 600°C to 800°C, and the nucleation time is 0.5h to 10h; the crystallization temperature is 700°C to 900°C, and the crystallization time is 0.1h to 4h.
9. A method for preparing tempered glass, characterized in that: The steps include: The glass-ceramics according to any one of claims 1 to 4 is subjected to chemical strengthening treatment.
10. A tempered glass, characterized in that: The method according to claim 9 is used to prepare the present invention.
11. Use of the glass-ceramics according to any one of claims 1 to 4, or the tempered glass according to claim 10, in the preparation of glass products.
